Chemical Characteristics, Sensory Analysis, and Antioxidant Activity Of Artificial Nori Made From Ptilophora pinnatifida With The Addition Of Moringa oleifera Leaves - Wulansari, Angela; Dewi, Eka Kusuma; Andriani, Rovina; Rasulu, Hamidin (Agrikan Jurnal Agribisnis Perikanan, 2022)
Ptilophora pinnatifida is a red algae that can be found in wild around Indonesia’s ocean. It is a potential raw material for artificial nori. The addition of Moringa oleifera leaves is needed to give green color similar to commercial nori. The aim of this study was produced artificial nori from Ptilophora pinnatifida and Moringa oleifera. This study was an experimental study with variation of Moringa oleifera concentration as the factor. There was three different concentrations of Moringa oleifera (4%, 6%, 8%). Artificial nori was tested for proximate analysis, antioxidant IC50 activity analysis, and Hedonic rating test. The result showed artificial nori had higher water, ash, carbohidrate, and crude fiber content than commercial nori. The protein and fat content of artificial nori were lower than commercial nori. Hedonic test result showed the color, texture, taste, and smell of artificial nori were slighly liked by the panelists. Artificial nori had low antioxidant activity compare to the standard Vitamin C, but artificial nori with 8% addition of Moringa oleifera had higher antioxidant activity than commercial nori. The best artificial nori which had the closest characteristics with commercial nori was artificial nori made from Ptilophora pinnatifida with 8% addition of Moringa oleifera.